2014
DOI: 10.3906/muh-1304-24
|View full text |Cite
|
Sign up to set email alerts
|

Chemically treated kola nut pod as low-cost natural adsorbent for the removal of 2,4-dinitrophenol from synthetic wastewater: batch equilibrium, kinetic, and thermodynamic modelling studies

Abstract: Abstract:The feasibility of using chemically treated kola nut pod to remove 2,4-dinitrophenol from its aqueous solutions under batch mode was investigated. The results showed that biosorption of 2,4-dinitrophenol was dependent on initial concentration, contact time, pH, biosorbent particle size, biosorbent dosage, and temperature. The batch equilibrium biosorption data were analyzed by 2 two-parameter (Langmuir and Freundlich) and 2 three-parameter (Redlich-Peterson and Sips) adsorption isotherm models using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…According to the interpretation of this three-stage process (Jiang et al, 2017; Lee, Lee, Chia, Tan, & Gan, 2014; Ngwabebhoh et al, 2016; Tang et al, 2012), the first stage (up to 60 minutes, 70% adsorption) is related to the diffusion of dye molecules from the bulk solution to the external surface of WPF/MMT. The second stage (up to 5 h, ~90% adsorption) can be attributed to intra-particle diffusion of dye molecules into the interior of WPF/MMT, and finally, the third linear stage is related to the equilibrium phase of the adsorption process and reflects the decrease in dye concentration (AGARRY & OGUNLEYE, 2014; Tang et al, 2012). Thus, it can be concluded that the adsorption data can be described with the intra-particle diffusion model.…”
Section: Resultsmentioning
confidence: 99%
“…According to the interpretation of this three-stage process (Jiang et al, 2017; Lee, Lee, Chia, Tan, & Gan, 2014; Ngwabebhoh et al, 2016; Tang et al, 2012), the first stage (up to 60 minutes, 70% adsorption) is related to the diffusion of dye molecules from the bulk solution to the external surface of WPF/MMT. The second stage (up to 5 h, ~90% adsorption) can be attributed to intra-particle diffusion of dye molecules into the interior of WPF/MMT, and finally, the third linear stage is related to the equilibrium phase of the adsorption process and reflects the decrease in dye concentration (AGARRY & OGUNLEYE, 2014; Tang et al, 2012). Thus, it can be concluded that the adsorption data can be described with the intra-particle diffusion model.…”
Section: Resultsmentioning
confidence: 99%
“…Batch adsorption studies were performed on a Tecnal Shaker (TE-421) with a temperature control device adjusted for different temperatures (288.15, 298.15, 308.15 and 318.15 K). Quinoline solutions of 5.00 mL prepared at different concentrations (4,12,20,28,36,44,52,60,68,76 and 82 mg L À1 ) were placed in contact with 10.00 mg of MIPC or MIPT adsorbent in amber asks under constant stirring at 180 rpm for four hours.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…Quinoline is one of the most powerful inhibitors of the HDT process due to poisoning of the catalysts. 4,5 Adsorption treatments using porous materials, such as zeolites, activated carbon, activated alumina, silica gel, kaolinite, and montmorillonite, are the preferred alternatives for the removal of these contaminants; however, they are not selective. 4,5 On the other hand, molecularly imprinted polymers (MIPs) are highly selective adsorbents because they are capable of forming complementary sites with the target molecule on their surfaces, which leads to the formation of specific cavities in the polymer network.…”
Section: Introductionmentioning
confidence: 99%
“…Freundlich adsorption isotherm can be applied for multilayer adsorption on heterogeneous surface with non-uniform distribution of adsorption heat [11], [12]. The linearity of Freundlich isotherm can be expressed by the following equation…”
Section: F Adsorption Isothermmentioning
confidence: 99%
“…Langmuir isotherm is based on monolayer adsorption on the active sites of adsorbent with a finite number of identical binding sites [11], [12]. ) where q e is the amount of As(V) adsorbed at equilibrium(mg/g), C e is the equilibrium As(V) concentration(mg/L), q m and b are Langmuir constants which represent the maximum adsorption capacity(mg/g) and the energy of adsorption, respectively.…”
Section: F Adsorption Isothermmentioning
confidence: 99%